Byzantine art - Bayet, Ch. (Charles), 1849-1918 (Art of century collection., 2009)
For more than a millennium, from its creation in 330 A.D. until its fall in 1453, the Byzantine Empire was a cradle of artistic effervescence that we are only beginning to rediscover. Endowed with the rich heritage of Roman, Eastern and Christian cultures, Byzantine artists developed an architectural and pictorial tradition, marked by symbolism, whose influence extended far beyond the borders of the Empire. Today, Italy, Northern Africa, and the Near East preserve the vestiges of this sophisticated artistic tradition, with all of its mystical and luminous beauty. The magnificence of the palace.